KINERJA KEUANGAN BANK SYARIAH DI ASEAN - Yessy Listiyanti; Atina Shofawati (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
The aims of this research is to determine differences in financial performancebetween Bank Islam Malaysia Berhad, Bank Syariah Mandiri, and Bank Islam Brunei Darussalam span from the period of 2011 to 2016. This study is a type of comparative research. Financial ratios used in this study are Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Return on Assets (ROA), Return on Equity (ROE), and Capital Adequacy Ratio (CAR). The statistical model used to test the hypothesis is the one-way ANOVA parametric test. The results showed that there were significant differences in all financial ratio indicators between the performance of Bank Islam Malaysia Berhad, Bank Syariah Mandiri, and Bank Islam Brunei Darussalam except ROA  REFERENCESAlamsyah, Halim. 2012. Perkembangan dan Prospek Perbankan Syariah Indonesia: Tantangan dalam Menyongsong MEA 2015. Makalah disajikan dalam Ceramah Milad ke-8 Ikatan Ahli Ekonomi Islam. Jakarta.Anshori, Muslich dan Sri Iswati. 2009. Buku Ajar Metodelogi Penelitian Kuantitatif.  Surabaya: Airlangga Uiversity Press.Antonio, Muhamad Syafi’i. 2007. Bank Syariah dari Teori ke Praktik. Jakarta: Gema Insani.Box, G. E. P. 1954a. Some Theorems on Quadratic Forms Applied in the Study of Analysis of Variance Problems: I. Effect of Inequality of Variances in the One-way Classification. Annals of Mathematical Statistics, 25, 290-302.Departemen Agama. 2010. Al-Qur’an dan Terjemahan. Bandung: Penerbit Hilal.Dewi, Dhika Rahma. 2010. Faktor-Faktor yang Mempengaruhi Profitabilitas Bank Syariah di Indonesia Periode 2005-2008. Skripsi tidak diterbitkan. Universitas Diponegoro.Ghozali, Imam. 2011. Aplikasi Analisis Multivariate dengan Program IBM SPSS 19. Semarang: Universitas Diponegoro.Ismail. 2011. Manajemen Perbankan: dari Teori menuju Aplikasi. Jakarta: Kencana.Jumingan. 2006. Analisis Laporan Keuangan. Jakarta: PT Bumi Aksara.Kasmir. 2008. Bank dan Lembaga Keuangan Lainnya. Jakarta: PT RajaGrafindo Persada.KFH Research. 2013. Islamic Finance in Asia: Development, Growth, and Opporunities. Kuwait: Kuwait Finance House.Lestari, Maharani Ika dan Toto Sugiharto. 2007. Kinerja Bank Devisa dan Bank Non Devisa dan Faktor-Faktor yang Mempengaruhinya. Jakarta: Universitas Gunadarma.Muhamad. 2015. Manajemen Dana Bank Syariah. Jakarta: Raja Grafindo Persada.Rosalia, Lia. 2011. Faktor-Faktor yang Mempengaruhi Profitabilitas Bank Syariah di Indonesia. Skripsi tidak diterbitkan. UIN Sunan Kalijaga Yogyakarta.Saniati, Resti. 2015. Analisis Eksternal dan Internal dalam Menentukan Non Performing Financing pada Bank Umum Syariah. Skripsi tidak diterbitkan. UIN Sunan Kalijaga Yogyakarta.Santoso, Singgih. 2014. Statistik Multivariat. Jakarta: Elex Media Komputindo.Shihab, M. Quraish. 2009a. Tafsirisl Al-Misbah. Vol. 2. Jakarta: Lentera Hati.Srimindarti, C. 2006. Balanced Scorecard Sebagai Alternatif untuk Mengukur Kinerja. Semarang: STIE Stikubank.Sukmana, Raditya & Nur Ahlina Febriyati. 2016. Islamic Banks vs Conventional Banks in Indonesia: An Analysis on Financial Performances. Jurnal Pengurusan, Vol. 47, hlm. 81-90. Wibowo, Susanto. 2015. Analisis Perbandingan Kinerja Keuangan Perbankan Syariah dengan Metode Camel di ASEAN (Studi Komparatif: Indonesia, Malaysia, Thailand). Journal of Research in Economics and Management, Vol. 15, No. 1, 2015, hlm. 136-153. Webster, Allen L. 1998.  Applied Statistics For Business and Economics: An Essentials Version. Singapore: Irwin McGrow-Hall.Regulasi Undang-Undang No. 21 Tahun 2008 SE OJK NO. 10/SEOJK.03/DPNP Tahun 2014 Internet http://www.asean.orghttp://www.bi.go.id http://www.bibd.com.bnhttp://www.bankislam.com.myhttp://www.banksyariahmandiri.co.idhttp://www.bnm.gov.my http://www.bps.go.idhttp://www.ekbis.sindonews.comhttps://www.ey.com http://www.focus-economics.comhttps://www.ifsb.comhttp://www.indonesia-investments.comhttps://www.kemenlu.go.idhttps://www.ojk.go.idhttps://www.rudiyanto.blog.kontan.co.id